Yiddish across borders: Interviews in the Yiddish ultra-Orthodox Jewish audio mass medium. (September 2017) - Assouline, Dalit; Dori-Hacohen, Gonen
Abstract: This study analyzes phone interactions in Yiddish that are broadcast by telephone to ultra-Orthodox Jewish communities through off-hook services called "hotlines". Yiddish, a minority language, is the native tongue of most hotline speakers and marks their communal affiliation within the ultra-Orthodox world. We explore the instrumentalities of one Yiddish hotline in order to ascertain features that facilitate its role as a membering medium for its community. We show how participants use this medium to index who is – and who is not – a community member via language decisions that reflect language ideologies and maintain community boundaries; interviewees index their membership by linguistically accommodating interviewers; and hosts, on occasion, change language to ostracize an interviewee. We also explore the problematic status of Modern Hebrew for this community. Highlights: We study Yiddish interviews broadcast by phone to ultra-Orthodox Jewish communities. Yiddish has symbolic value as the unifying language of a Hasidic global community. Language choices in the interviews index who is (and who is not) a community member. Interviews reflect the problematic status of Modern Hebrew for this community.